2013
DOI: 10.1186/1476-0711-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Application of ATC/DDD methodology to eveluate of antibiotic use in a general hospital in Turkey

Abstract: BackgroundThe aim of this study is to evaluate in-house antibiotic use in a state hospital in Turkey with its cost, using the ATC/DDD index, which is an accepted standard method.MethodsThis study was performed as a point prevalence study in a state hospital with 372 beds. All in-house patients using antibiotics on July 19, 2011 were included in the study. Indications for antibiotic use and information about the patients were recorded on special forms. Antibiotic use and cost analysis were evaluated using the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
1
31
1
3
Order By: Relevance
“…In our study, both the average duration of chemoprophylaxis (2.78 days: minimum 1, maximum 13 days) and empirical therapy (4.75/4.85 days: minimum 1, maximum 20 days) are longer in HA sub-samples (SIII, SIV). This situation is also found in other countries in the region, as can be seen in a Turkish study published in 2013, which identified a perioperative prophylactic antibiotic treatment duration of 4.74 days (minimum 1 and maximum 17 days) [14]. In our case, we noticed situations when clinicians avoid de-escalation, especially in patients with favourable evolution under empirical antibiotic treatment.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, both the average duration of chemoprophylaxis (2.78 days: minimum 1, maximum 13 days) and empirical therapy (4.75/4.85 days: minimum 1, maximum 20 days) are longer in HA sub-samples (SIII, SIV). This situation is also found in other countries in the region, as can be seen in a Turkish study published in 2013, which identified a perioperative prophylactic antibiotic treatment duration of 4.74 days (minimum 1 and maximum 17 days) [14]. In our case, we noticed situations when clinicians avoid de-escalation, especially in patients with favourable evolution under empirical antibiotic treatment.…”
Section: Discussionsupporting
confidence: 81%
“…A study concluded that, DDD methods are useful for benchmarking purposes and do not imply the number of Days of Therapy (DOTs) or relative use for many antibacterial drugs [14]. Also, many studies demonstrated the use of DDD for measuring the Antibiotic consumption [12,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore antibiotic consumption studies are done mainly to identify areas of improvement, to compare antimicrobial use across wards and hospitals, [17] to study impact of interventions [16] and capture attention of healthcare professionals on its rational use. [18] The data of the present study was recorded over twelve months .In the first six months i.e January to June, a total of 30973 in-patients were recorded; whereas there was an increase in number in in-patients in the next six months (33813 in-patients).The antibiotics in both the periods antibiotics were most frequently used for post -surgical patients (29.25% and 21.16 % respectively) by various surgical departments (viz. surgery, orthopedics and obstetrics -gynecology).…”
Section: Discussionmentioning
confidence: 99%